Assessment and interpretation of sleep disordered breathing severity in cardiology: Clinical implications and perspectives. (15th November 2018) - Linz, Dominik; Baumert, Mathias; Catcheside, Peter; Floras, John; Sanders, Prashanthan; Lévy, Patrick; Cowie, Martin R.; Doug McEvoy, R.
Abstract: Sleep disordered breathing (SDB) is highly prevalent in patients with atrial fibrillation, heart failure and hypertension and is associated with increased risk of mortality, cardiovascular (CV) events and arrhythmias. Current assessment of the severity of SDB is mainly based on the apnea-hypopnea index (AHI) representing the number of hypopneas and apneas per hour of sleep. However, this event-based parameter alone may not sufficiently reflect the complex pathophysiological mechanisms underlying SDB potentially contributing to CV outcome risk. In this review article, we highlight important limitations and pitfalls of current assessment, quantification and interpretation of SDB-severity in patients with CV disease and will discuss pathophysiological considerations from preclinical and clinical mechanistic studies and possible clinical implications. Highlights: Sleep apnea is highly prevalent in patients with arrhythmias and cardiac disease. The apnea-hypopnea index does not sufficiently reflect sleep apnea severity. Nocturnal hypoxemia and sleep apnea burden may have additional prognostic value. Better metrics are needed to guide and predict response to treatment in cardiology. Sleep apnea management requires a multidisciplinary approach.